Envolvimento do receptor de potencial transitório de anquirina 1 na nocicepção e inflamação induzida pela radiação ultravioleta B em camundongos - Fialho, Maria Fernanda Pessano (2019)
Burn injuries cause psychological and economically impacts since is characterized as debilitating and lifelong injuries causing dramatic clinical effects in humans. These injuries can be caused by several factors, chemicals substances, fire, scald, contacts with hot surfaces or ultraviolet (UV) radiation. Ultraviolet B (UVB) radiation exposure promotes sunburn and thus acute and chronic inflammatory processes contributing to pain development and maintenance. Sunburn pharmacological treatments currently available are used to alleviate the patients’ discomfort (pain and inflammation). However, these therapies are associated with adverse effects that limit their use. For this reason, it is relevant to identify new molecular targets to treat inflammatory pain conditions, including sunburn. A potential therapeutic target is the transient receptor potential ankyrin 1 (TRPA1), which is involved in a variety of inflammatory pain models. TRPA1 channel is activated by exogenous irritants compounds, extracellular Ca2+ influx and several endogenous oxidant molecules that are produced during tissue damage and inflammation, as by UV radiation. We evaluated the peripheral participation of TRPA1 using a topical treatment containing 0.05% HC030031 (a selective TRPA1 antagonist) on nociception and inflammation caused by a UVB radiation-induced burn model in male mice (25-30g), approved by Institutional Committee for Animal Care and Use-UFSM (protocol number 2479201217/2018). The mice were anesthetized and just the right hind paw was exposed to UVB radiation for 21 minutes (0.75 J/cm2). The topical treatments with different gels formulations (base gel, silver sulfadiazine 1%; positive control, HC030031 0.05%) were applied once a day for 8 days. Nociceptive (mechanical and cold allodynia and thermal hyperalgesia) and inflammatory (edema measurement) parameters were evaluated during 8 days always at 24h after topical treatment. The inflammatory cell infiltration was evaluated by myeloperoxidase (MPO) enzyme activity and histological analysis at 24h after UVB radiation. H2O2 levels (a TRPA1 agonist) in the irradiated paw tissue, and Ca2+ influx in mice spinal cord synaptosomes were determined to evaluate a possible mechanism of activation TRPA1 channel by UVB radiation. The gels formulations stability was also evaluated. The HC030031 0.05% reversed the mechanical and cold allodynia UVB-radiation induced with maximum inhibition (Imax) of 69±13% and 100% (4th day), respectively. HC030031 0.05% also reduced the paw edema and MPO activity with Imax of 77±6% on the 5th day and 69±28%, respectively. The reduced leukocyte infiltration was confirmed by histological analysis at the paw tissue. The UVB radiation increased the H2O2 levelsand the Ca2+ influx in mice spinal cord synaptosomes. The UVB radiation-induced Ca2+ influx was reduced by HC030031. HC030031 gel presented suitable pH and spreadability factor ensuring its quality and the therapeutic effect. Our results confirm the activation of the TRPA1 channel by UVB radiation, suggesting that topical TRPA1 antagonists can be a new strategy or therapy for the adjuvant treatment of the sunburn-associated pain and inflammation.